Unmet need for contraception? Understanding postpartum family planning desires and use in Kumasi, Ghana - Guzman, Natalie M.; Nakua, Emmanuel; Moyer, Cheryl A.; Lori, Jody R.; Dzomeku, Veronica; Otupiri, Easmon; Compton, Sarah D. (Frontiers in Reproductive Health, 2025)
IntroductionWhile most postpartum women in Ghana report they would like to limit or space their births, few are using a highly effective method of family planning. We sought to better understand the reasons behind these seemingly contradictory stances.MethodsWe interviewed 48 postpartum women who had given birth 3–6 months prior and were seeking childhood immunization services at 2 hospitals in urban Kumasi, Ghana. Participants offered their opinions on previous, current, and future family planning use. Interviews were conducted by a trained, bilingual, female research assistant after the infant's appointment in a private room near the Child Welfare Clinic. Interview data were translated and transcribed verbatim and analyzed thematically using NVivo 14.0.ResultsWhile all participants reported wanting to wait at least 2 years before becoming pregnant again, only 3 were currently using a method of modern contraception. Many of our participants expressed aversion to contraception, driven mainly by the perceived risk of contraception being dangerous to their health and future fertility as reported by members of their social network. Many of those, however, were using either fertility-awareness-based methods, emergency contraception, condoms, or some combination. Those who had had negative personal experience with modern contraceptives were reluctant to use it again due mainly to menstrual side effects. Additionally, some participants had no reason for not wanting to use contraception, they simply do not want to.DiscussionThis qualitative study of women in Kumasi, Ghana, provides a framework to better understand family planning readiness and need. Many participants expressed limited knowledge about modern contraception, highlighting the importance of tailoring counseling to address women's unique questions and concerns. Potential contraceptive users appeared open to and curious about modern methods but had been deterred by stories and misconceptions about adverse consequences. Some women simply chose not to use contraception. Ensuring women have complete, unbiased information on which to base their decisions about contraceptive use and method selection represents a promising avenue for future interventions that seek to improve women's ability to meet their fertility goals.